Bedouin Poetry as an Art of Memory. The Dialogue between the Present and the past in the Political Poetry of the Negev Bedouin - Kobi Peled (Nomadic Peoples, 2024)
Bedouin poetry has yet to be explored in the context of memory studies, let alone the poetry of the Negev Bedouin. This article, based on a corpus of hundreds of poems documented between the mid-1940s and late-1980s, reviews excerpts from ten political verses composed by Negev Bedouin poets. These verses attest to the power of Bedouin poetry to evoke – at times in just a word or two – a wide range of meanings, a historical depth that may be submersed in a few expressions, and the ways in which these expressions activate memories of the past to communicate something of significance about the present.